Dedifferentiation of oncocytic epithelial-myoepithelial carcinoma to mucoepidermoid carcinoma in parotid gland: A rare case report - Poonam Rani; Meeta Singh; Chetna Mehrol; Amita Jain Gupta; Nita Khurana; Ravi Meher (Wolters Kluwer Medknow Publications, 2018)
Epithelial-myoepithelial carcinomas (EMCs) account for <1% of all salivary gland malignancies. Till now, 23 cases of dedifferentiated EMC have been reported to the best of our knowledge. However, dedifferentiation of oncocytic EMC to mucoepidermoid carcinoma is extremely rare. A 38-year-old female presented with right post aural swelling 4 cm × 2 cm in size for 6 months. Surgical excision was carried out, and we received partly skin-covered tissue 5 cm × 2 cm in size. Sections examined showed features of oncocytic EMC dedifferentiating into mucoepidermoid carcinoma. Myoepithelial component showed oncocytic change which was highlighted by p63.